Barriers to practice of critical newborn care behaviours: findings from a qualitative assessment in rural Madhya Pradesh, India - Chatterjee, Nilesh; Singh, Sanjay; Fernandes, Genevie (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, the state of Madhya Pradesh has one of the highest infant mortality rates (IMR) as compared to the national average. About two out of every three infant deaths in Madhya Pradesh, are of neonates. Given the high neonatal mortality rate in the state, this study aimed to explore the perceptions, practices, barriers and enablers related to critical newborn care behaviors, such as cord-care, thermal care, skin-to-skin care, and early initiation of breastfeeding, in the first 24 hours of life. Methods: In-depth interviews and focus group discussions were conducted with 53 respondents including mothers and fathers of the newborn, mothers-in-law, elected community and tribal leaders, local NGO representatives, and frontline health workers, in two districts of Madhya Pradesh. Results: Few mothers knew about the benefits of cord care, thermal care and early initiation of breastfeeding. Fathers lacked knowledge and perceived newborn care as the mother’s responsibility. Skin-to-skin care was rarely practiced; and was perceived across respondent groups as necessary only for weak infants. Older women, influential in decision making in the household, held misconceptions about thermal care and breastfeeding practices. Traditions and social norms emerged as major barriers while institutional delivery served as an enabling factor for the practice of correct newborn-care behaviors. Conclusions: To increase adoption of critical newborn behaviours, health care providers will have to move beyond mere interpersonal communication with individual mothers at facility or household levels towards a community and societal approach. A strategic behaviour change communication program that addresses deep-rooted traditional and social norms is required to help the state reduce infant deaths.